Enhancing Audit Report Quality through Auditor Professionalism: Regional Inspectorate Office of Central Sulawesi Province Evidence - Ribi Awad; Muhammad Ansar (Journal GoodWill, 2024)
This study examines the influence of independence, competence, and accountability on audit quality among auditors at the Regional Inspectorate Office of Central Sulawesi Province. Using a quantitative approach with a survey design, data were collected through questionnaires distributed to 40 auditors and analyzed using multiple linear regression with SPSS 25. The results indicate that independence, competence, and accountability simultaneously have a significant effect on audit quality. Partially, competence and accountability show a positive and significant influence, while independence does not significantly affect audit quality. The findings reveal that competence and accountability are critical determinants of high-quality audit outcomes, reflecting the importance of continuous professional development and ethical responsibility among auditors. The coefficient of determination (R²) value of 0.894 demonstrates that 89.4% of variations in audit quality can be explained by these three variables. This study contributes to strengthening the theoretical framework of public sector auditing by emphasizing the role of auditor professionalism in enhancing transparency and governance. It also provides practical implications for improving the performance of internal government auditors through targeted training programs and reinforcement of accountability mechanisms. Future research is suggested to explore other factors, such as organizational culture, leadership style, and digital audit systems, which may further influence the quality of audit results in public institutions.